Correlation between burden and sleep quality in informal caregivers of infants with orofacial cleft - Nayara Tomazi Batista; Ana Flávia Martinez; Gesiane Cristina Bom; Francely Tineli Farinha; Priscila Capelato Prado; Armando dos Santos Trettene (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To evaluate the correlation between burden and sleep quality in caregivers of infants with cleft lip and/or palate. Methods: This descriptive cross-sectional study was carried out in a Brazilian tertiary public hospital between March and September 2020. The sample included the main informal, literate caregivers of infants with cleft lip and/or palate, aged 18 years or older. The instruments used were the Burden Interview Scale and the Pittsburgh Sleep Quality Index. Data were collected during the infants' hospitalization. Statistical analysis adopted Pearson and Spearman correlations, with a 5% significance level. Results: A total of 31 informal caregivers participated in the study, most of them mothers (n=28; 90%), with a mean age of 30 years (standard deviation - SD=7.5), low socioeconomic status (n=20; 64%), who completed high school (n=19; 61%), were married (58%), had two children (n=15; 48%), and no employment relationship (n=18; 58%). A moderate correlation was found between sleep quality and burden (r=0.39; p=0.032) and between burden and subjective sleep quality (r=0.39; p=0.029), sleep latency (r=0.43; p=0.017), and daytime dysfunction (r=0.49; p<0.001). Conclusions: The study showed that the higher the burden, the lower the sleep quality. The findings indicate the need to plan and implement interventions to minimize the burden experienced by these informal caregivers in order to improve their sleep quality.